Visceral Kaposi Sarcoma Presenting as Small Bowel Intussusception: A Rare Presentation and Call to Action. Issue 7 (July 2019) - Lovasik, Brendan P.; Wang, Vivian L.; Du Jour, Kimberly S. Point; Kim, Steven C.; Hashmi, Salila S.; Haack, Carla I.
Surgical emergencies related to visceral involvement of Kaposi sarcoma (KS) are rare complications of the disease. In this report, we describe a case of visceral KS causing small bowel intussusception in a young, previously undiagnosed human immunodeficiency virus (HIV)–positive patient. Southern surgeons should be particularly attentive to HIV/AIDS-related disease as a cause of surgical pathology, particularly in the southeast, and can play a significant advocacy role for improved access to HIV/AIDS diagnostic and treatment services.